Czy człowiek musi się zmagać ze swoimi genami? - Józef Wróbel (Jesuit University Ignatianum in Krakow, 2017)
Ideas propagated by neoeugenics were and are provoking moralanxiety.Moreandmoreclearly,geneticists'achievements arecomingnearertheboundary,wherebiologicalthinkingclearly demandsphilosophicalthinkingandtheanswertotwoquestions: iseverythingthatistechnicallypossibleatthesametimemorally permitted and to what extent do the genes create a human person?Atfirstglancetheanswerappearssimple.Whomanisand what kind of person he is, man owes to his genes. However,theauthordoesnotsharethisstandpoint.Hethinks that the relation between genes and person can be settled only fromtheoverall,i.e.philosophical,visionofanindividualperspective,characteristicofChristianpersonalism.Inhisviewpoint,anindividualconstitutesaspiritual-bodilyunity,whichmeansthatman isnotmerelyhisbiology;consequently,notonlyhisgeneseither. In the such outlined perspective, human genetic structure is understood as an element of his bodily structure. According to the author, attempts to modify human genetic reserve would bring about not only an disproportionately large risk, but also cannot agree with his personal dignity. Man can never be reducedtothelevelofanobjectwhichcanbetakenintopossession and programmed up to the standards of the subjective criteria established by somebody else.